2020
DOI: 10.1109/access.2020.3014396
|View full text |Cite
|
Sign up to set email alerts
|

Channel Selection Decision in a Dual-Channel Supply Chain: A Consumer-Driven Perspective

Abstract: In a supply chain, customers have heterogeneity preferences due to channel stickiness and brand stickiness. The complicated behaviors of different customers (i.e., target customers and experience customers) results can lead to channel cannibalization, which increases the difficulties of manufacturers choosing between traditional channel and dual-channel supply chain. Therefore, to examine this claim more carefully, we develop Stackelberg game models to analyze channel selection decisions under the monopoly com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Cai [2] noted that the dual-channel structure is superior to any single-channel structure without competition. Yong-Shi Hu [3] points out that under the monopoly competition, the expected profits of experiential customers cannot be maximized, and a single online channel is not the dominant choice of monopolies. Based on industry data, some scholars have found that dual-channel retailers can improve customer satisfaction compared to single-channel retailers, so multichannel retail is a useful strategy to build customer loyalty [4], which also helps improve the "barriers" to new market entry and enhance the competitive position of retailers.…”
Section: Introductionmentioning
confidence: 99%
“…Cai [2] noted that the dual-channel structure is superior to any single-channel structure without competition. Yong-Shi Hu [3] points out that under the monopoly competition, the expected profits of experiential customers cannot be maximized, and a single online channel is not the dominant choice of monopolies. Based on industry data, some scholars have found that dual-channel retailers can improve customer satisfaction compared to single-channel retailers, so multichannel retail is a useful strategy to build customer loyalty [4], which also helps improve the "barriers" to new market entry and enhance the competitive position of retailers.…”
Section: Introductionmentioning
confidence: 99%